2017
DOI: 10.1002/jemt.22871
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neem oil (Azadirachta indica A. JUSS) enriched with different concentrations of azadirachtin on the integument of semi‐engorged Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) females

Abstract: Several studies searching for methods to control Rhipicephalus sanguineus s.l., (dog tick) infestations have been developed aiming to minimize the damages caused by these ectoparasites to the hosts and the environment, which is harmed by the indiscriminate use of toxic acaricide products. In this scenario, neem oil has been used as a natural alternative against ticks, once this chemical has repellent properties and interferes in the growth regulation of these ectoparasites, inhibiting ecdysis. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
(67 reference statements)
1
6
0
1
Order By: Relevance
“…This layer, originally composed of a simple cubic epithelium, became stratified, presenting cells of various sizes and containing pyknotic nuclei, indicating, in addition to structural disorganization, cell death. This demonstrated that the investigated bioactive compound was able to alter cuticle permeability, crossing this layer and reaching the epithelial cells, as reported by Lima de Souza et al (2017) when exposing female R. sanguineus s.l. ticks to neem oil enriched with azadirachtin at different concentrations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This layer, originally composed of a simple cubic epithelium, became stratified, presenting cells of various sizes and containing pyknotic nuclei, indicating, in addition to structural disorganization, cell death. This demonstrated that the investigated bioactive compound was able to alter cuticle permeability, crossing this layer and reaching the epithelial cells, as reported by Lima de Souza et al (2017) when exposing female R. sanguineus s.l. ticks to neem oil enriched with azadirachtin at different concentrations.…”
Section: Discussionsupporting
confidence: 83%
“…In this perspective, the use of bioactive compounds present in the extracts and oils of several plants has been considered for use in tick control, as these compounds can interfere in the metabolism of various tick organs, modifying their physiology and making them more vulnerable, in addition to preventing successful feeding and reproduction processes. Furthermore, the use of bioactive compounds results in less environmental effects since they are easily degradable, generating less soil, air, and water residue accumulation (Anholeto et al, 2017; Lima de Souza et al, 2017; Remedio et al, 2014; Rosado‐Aguilar et al, 2017). In this regard, laboratory assessments have demonstrated that plants belonging to the Lamiaceae and Verbenaceae families are strong candidates for the provision of acaricide bioactive compounds, as they present the monoterpene carvacrol, which displays several biological properties, including acaricidal, as their main active ingredient (Koc et al, 2013; Martinez‐Velazquez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar outcomes were reported after treatment with neem oils containing Azadirachtin [ 150 ], indicating that the changes in morphology are possibly connected with this compound. Furthermore, neem oil also reduces cuticle thickness and distorts epithelial cell morphology of semi-engorged females [ 151 ]. However, neem leaf extracts can negatively affect oocytes and ovaries in mammals.…”
Section: Plant-derived Compounds With Potential Use For Tick Pest mentioning
confidence: 99%
“…Azadirachta indica has major ectoparasiticides in its various parts, especially in seeds and leaves. Herbal combinations containing A.indica has been found quite useful and efficacious against ectoparasites such as nymphal ticks, fleas, lice and mites (Abdel-Ghaffar et al, 2008;Bhilegaonkar and Maske, 1997;Habluetzel, et al, 2007;Kilonzo, et al, 2001;Lima de Souza et al, 2017). The aqueous extract of A. indica has been shown to have activity against the maturation of parasite oocytes, the oviposition, the reproductive potential and embryonic development of a fish ectoparasite (Banerjee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…. AZEEM, H. AKBAR, L. AHMAD, M. ASHRAF, S. PUVANENDIRANnan et al, (1996),Borges et al, (2003) and Lima deSouza et al (2017).…”
mentioning
confidence: 99%